Ability of Layperson Callers to Apply a Tourniquet Following Protocol-Based Instructions From an Emergency Medical Dispatcher. (1st November 2020) - Scott, Greg; Olola, Christopher; Gardett, Marie Isabel; Ashwood, Daniel; Broadbent, Meghan; Sangaraju, Srilakshmi; Stiegler, Paul; Fivaz, Mark Conrad; Clawson, Jeff J.
Abstract: Introduction : One of the greatest casualty-care improvements resulting from US military operations in Iraq and Afghanistan has been the reduction of preventable death from massive extremity hemorrhage – largely due to the widespread use of limb tourniquets. More recently, tourniquet use in civilian, prehospital settings has shown promise in reducing deaths in cases of catastrophic arterial limb hemorrhage. Telephone instructions by trained emergency medical dispatchers (EMDs) on applying an available tourniquet may help achieve such a benefit. Objectives : The objective of the study was to determine whether layperson callers can effectively stop simulated bleeding using an improvised or a commercial tourniquet, when provided with scripted instructions via phone from a trained protocol-aided EMD. Methods : This was a prospective, randomized trial involving layperson volunteers, done at four locations in Salt Lake City, Utah, USA. Volunteers were assigned randomly to three groups: one for each of two commonly available commercial tourniquets and one for an improvised tourniquet. Results : A total of 246 subjects participated in the study at the four locations between February 11, 2019 and June 22, 2019. The overall median time for all trials (i.e., elapsed time from the start to the end of the simulation) was 3 minutes and 19 seconds. Median time to stop the bleeding (i.e., elapsed time from the start of the simulation to the time the participant was able to successfully stop the bleeding) was 2 minutes and 57 seconds. Median tourniquet pressure was 256 mmHg and median-end blood loss was 1, 365 mL. A total of 198 participants (80.49%) were able to completely stop the bleeding while 16 participants (6.5%) had the tourniquet applied with some bleeding still occurring, and 32 participants (13.01%) exceeded the threshold of 2, 500 mL of blood loss, resulting in the "patient" not surviving. Conclusions : The study findings demonstrated that untrained bystanders provided with instructions via phone from a trained Emergency Medical Dispatcher applied a tourniquet and successfully stopped the bleeding completely in most cases.